Gen-z dan pancasila: menciptakan inovasi sosial untuk masyarakat mewujudkan indonesia emas 2045 - islami, muhammad shokhikhul islami shokhikhul; Al Mahbubi, Muhammad Rusydan (Maliki Interdisciplinary Journal, 2025)
Preparing the younger generation to achieve the vision of Indonesia 2045 is a complex challenge facing the country. The rapidly growing phenomenon of globalization has had a significant impact, especially among generation Z - namely those born between 1996 and 2012 (Marpaung & Rahma, 2023). This research aims to analyze the characteristics of generation Z in Indonesia, as well as how they can integrate Pancasila values to create social innovation in realizing a Golden Indonesia 2045